Research handbook on the international law of indigenous rights - Newman, Dwight (Research handbooks in international law series, 2022)
This ground-breaking Research Handbook provides a state-of-the-art discussion of the international law of Indigenous rights and how it has developed in recent decades. Drawing from their extensive knowledge of the topic, leading scholars provide strong general coverage and highlight the challenges and cutting-edge issues arising for Indigenous peoples. Offering readers an engaging review of ongoing lawmaking, adoption and implementation processes from both a global and regional perspective, it also investigates the important elements of Indigenous rights and economic issues, including trade, investment and economic growth. Furthermore, it offers timely coverage of environmental rights, land and natural resources. This essential Handbook will provide a useful discussion point for practitioners on Indigenous rights developments and scholars looking for an innovative approach on cutting-edge issues. Policy-makers wanting to understand the major issues with the implementation of the UN Declaration on the Rights of Indigenous People (UNDRIP) will also find this invaluable.